PENGARUH KERAGAMAN PRODUK, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA KEDAI NENG IRMA DI KOTA SITUBONDO - Fatmasari Fatmasari; Edy Kusnadi Hamdun; Lusiana Tulhusnah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The results of multiple linear regression indicate that the product diversity (X1), service quality (X2), and price (X3) variables have a positive influence on the Consumer Satisfaction variable (Y) it is shown in the results of multiple linear regression analysis Y= 4.026E-16 + 0.264X1 + 0.157X2 + 0.520X3 + e. shows the value for the product diversity variable is t_count 3.333 > t_table 1.985, meaning that the product diversity variable has a partial effect on consumer satisfaction. The value for the service quality variable is t_count 2.168 > t _table 1.985, meaning that the price variable has a partial effect on consumer satisfaction. The value for the price variable is t_count 6.709 > t_table 1.985, meaning that the price variable has a partial effect on consumer satisfaction at Kedai Neng Irma in Situbondo. The F test shows the value of Fcount 38.748 > Ftable 2.70, so it can be concluded that the research hypothesis (H2) which states that the variables of product diversity, service quality and price have a simultaneous effect on consumer satisfaction. Based on the dominant test, the value of the price variable is greater than the other variables of 6.709. The coefficient of determination or R square shows a value of 0.550 from these results, meaning that all independent variables (product diversity, service quality and price) have a contribution of 55,0% to the dependent variable (customer satisfaction) with a level of influence "strong enough", and the rest of 45,0% influenced by other variables not included in the study.